2011 Review of Conditionality : Technical Appendices. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This section provides the background studies relating to dimensions of Fund policy on conditionality. Appendix 1 provides a review of Fund experience with coordination, both in a low-income country (LIC) setting (in African programs) and in an emerging market and advanced economy setting in the European Union (EU) and Euro Area (EA). Appendix 2 summarizes the recent changes to debt limits in LICs and provides an assessment of the implementation of this policy in the early stages (up to mid-February 2011). Appendix 3 reviews the experience of countries with the Flexible Credit Line (FCL) and Precautionary Credit Line (PCL)-supported programs. Appendix 4 examines the impact of the 2009 Special Drawing Rights (SDR) allocation on program design.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet